Basic elements of narrative - Herman, David, 1962- (Wiley-Blackwell, 2009)
"Basic Elements of Narrative outlines a way of thinking about what narrative is and how to identify its basic elements across various media, introducing key concepts developed by previous theorists and contributing original ideas to the growing body of scholarship on stories are told and interpreted exchanged and transformed."